The Chemical Literacy Understanding of Chemistry Teachers at Islamic Senior High School - Mahbub Alwathoni; Sulistyo Saputro; Sri Yamtinah; Mohammad Masykuri (International Journal of Science and Applied Science: Conference Series, 2020)
Chemical literacy has a role in helping students understand local and global issues such as the energy crisis, environment, and health. Teachers need an adequate understanding of chemical literacy to plan appropriate learning and design adequate assessment instruments. This study aims to analyze the description of chemical literacy skills in chemistry teachers at Madrasah Aliyah (Islamic Senior High School). This research is a quantitative descriptive method that describes the understanding of chemical literacy. A total of 85 teachers from 12 Madrasah Aliyah in Central Java, Indonesia were respondents. The research data were obtained by questionnaire with a total of 24 statements about the components of chemical literacy. Questionnaire analysis carried out to see the relationship between teacher understanding in assessing chemical literacy, obtained by using RASCH analysis. The results showed that the reliability of the questionnaire was 0.98. Cronbach's Alpha (α) which measures the interaction between respondents and items has a value of 0.96. This value indicates the instrument used is in perfect condition and effective with a high level of reliability so that it can use in actual research. The results showed that the teachers had not fully understood the domains and aspects of chemical literacy skills. The Wright map shows only 30% of respondents (teachers) understand the aspects of chemical literacy and apply them in chemistry learning. The results of this study suggest that policymakers such as the government and educational institutions, hold more in-house training and workshops on chemical literacy for teachers.